Intangible assets in Germany – Analysis of the German stock market index DAX and a survey among the German Certified Public Accountants. Issue 2 (19th August 2014) - Frey, Hannes; Oehler, Andreas; Mundy, Julia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Intangible assets are regarded as the future value drivers of company performance. However, hardly anything is known about the actual importance and influence of intangible assets. To fill this gap we analyse the German stock market index DAX and accomplish a survey among the German Certified Public Accountants (CPAs) concerning intangible assets. Design/methodology/approach In a first step, we analyse the balance sheet data and the corresponding notes of the companies with regard to reported values of intangible assets and applied valuation methods. The sample period covers the years from 2005 to 2008. In a second step, we analyse the statements of the German CPAs with regard to intangible assets. We sent a standardized questionnaire to all 180 offices of the top ten German auditing firms. Findings Our results indicate that intangible assets have gained in importance, while information on valuation methods is still scarce. According to the German CPAs, the current influence of intangible assets on company performance is on a high level and even will increase during the next few years. The mostly used valuation approach for the fair value measurement of patented technologies is the income approach. Furthermore, the accounting standards leave room for accounting policy – a result which casts doubt on the reliability of financial statements. Originality/value For the first time not only annual balance sheet data but also corresponding notes regarding intangible assets are analysed. The findings are connected with a survey of an expert group for the valuation of intangibles.